The motive of competition but not courtship positively correlates with self-reported use of aggressive humor: A critical test of the contests- vs. mate-choice hypotheses - Duarte, Brent; Zhang, Jinguang (Frontiers in Psychology, 2023)
The use of aggressive humor (e.g., teasing, schadenfreude, and sarcasm) is a spiteful behavior because it inflicts costs on both others and the self. To explain the existence of this spiteful behavior, two hypotheses derived from sexual selection theory—namely Mate-Choice and Contests—posit that the use of aggressive humor helps one attract mates or repel competitors. Both hypotheses have merit, but extant data are unable to discriminate between them. We critically tested those two hypotheses with a survey study that measured 509 U.S. MTurkers’ self-reported tendencies to use aggressive (and other types of) humor, the motives to engage in competition and courtship, and the Dark-Triad personality traits. With a final sample of N = 439, we found that 1) the motive of competition but not courtship positively and significantly correlated with the self-reported tendency to use aggressive humor. 2) Subclinical psychopathy—a personality trait positively associated with competition—mediated the correlation between the motive of competition and self-reported use of aggressive humor. These results, which were held in both female and male respondents, favored the Contests Hypothesis and helped reveal the psychological mechanism that generates the use of aggressive humor as a form of verbal aggression.